Study of structural, microstructure, impedance, and DC conductivity of Gd-doped SrCeO3 ceramics - Yadav D.; Nirala G.; Yadav S.; Kumar U.; Upadhyay S.; Kumar S. (My University, 2025)
Samples of the system SrCe1−xGdxO3 (x = 0.0, 0.02, 0.04, 0.06 and 0.10) were prepared using a conventional ceramic route. The phase and structural properties of samples were investigated using X-ray diffraction. Rietveld refinement of the XRD data supported the crystallization of samples in an orthorhombic structure under space group Pnma. FTIR and TGA measurements indicated the presence of SrCO3 in all the samples. The incorporation of Gd into the lattice was shown to reduce the direct optical bandgap and average grain size. The DC conductivity of the cylindrical pellets of samples was investigated using AC impedance measurements at temperatures ranging from 300 to 600 °C. The highest conductivity was observed for the composition SrCe0.98Gd0.02O3 such as 1.54 × 10−3 Scm−1 at 600 °C. This compound has the potential to be work as mixed ionic and electronic conductor for SOFCs. The XPS spectra of Ce 3d and O 1 s confirmed the presence of Ce in both Ce3+ and Ce4+ states and oxygen vacancies. The oxygen vacancies in the samples were analyzed using Raman spectroscopy. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.